2019
DOI: 10.1039/c9nj00886a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a cationic organic network for highly efficient removal of anionic contaminants from water

Abstract: A new cationic organic network is constructed by a facile method from commercially available precursors, and exhibits high efficiency for removal of water contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…To gain insight into the role of hydrogen bonding interactions within trimesic amide in the formation of infinite 2D polymeric structure, cationic COP 2 without any hydrogen bonding based on the polymerization of C 3 -symmetric 1,3,5-tris­(4-pyridylethynyl)­benzene (TPB) was prepared . As expected, 2 formed into randomly interconnected isotropic spherical aggregates, which was confirmed by DLS, zeta potential, SEM, and TEM (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain insight into the role of hydrogen bonding interactions within trimesic amide in the formation of infinite 2D polymeric structure, cationic COP 2 without any hydrogen bonding based on the polymerization of C 3 -symmetric 1,3,5-tris­(4-pyridylethynyl)­benzene (TPB) was prepared . As expected, 2 formed into randomly interconnected isotropic spherical aggregates, which was confirmed by DLS, zeta potential, SEM, and TEM (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Among aforementioned materials, cationic COPs are the most widespread adsorbent due to their simple preparation, high dispersity, as well as large surface area. 12,13 Although linear, cross-linked, and branched cationic polymers with remarkably enhanced removal capacity for anionic pollutants have been employed, part of the cationic sites are hidden by randomly interconnected polymeric chains, which cause the reduced adsorption ability. Two-dimensional (2D) cationic polymers are one of the promising candidates due to their high surface area, 14 but 2D cationic polymerization is challenging to realize without a special template.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have also been reported regarding the adsorption of different dyes, originating mainly from the paper, paint and clothing industries, namely, Congo red (CR), methyl orange (MO), orange G (OG) and indigo carmine (IC). Polycationic COFs were synthesized for the removal of anionic dyes, with excellent adsorption capacities and recyclability [ 73 , 74 ], as well as COFs functionalized with electron-withdrawing groups for the adsorption of cationic dyes [ 75 ] and COFs impregnated with metal ions to promote favorable metal-dye coordination interactions [ 76 ].…”
Section: Cof Applicationsmentioning
confidence: 99%
“…, dexamethasone derivatives) and pollutants ( e.g. , toxic oxo-anions and dyes) are highly demanded; however, such structures are rarely reported compared to the anionic and neutral frameworks.…”
mentioning
confidence: 99%